2008
DOI: 10.2310/jim.0b013e31816d78e9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additive Therapy with Spironolactone on Proteinuria in Diabetic Patients Already on ACE Inhibitor or ARB Therapy: Results of a Randomized, Placebo-Controlled, Double-Blind, Crossover Trial

Abstract: Addition of a modest dose of spironolactone to a regimen of ACEI or ARB in patients with diabetic proteinuria causes further reduction in proteinuria and also lowers the systolic BP. As with ACEI or ARB, spironolactone modestly reduces the glomerular filtration rate and raises serum potassium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 41 publications
2
39
0
1
Order By: Relevance
“…GFR was decreased in the spironolactone group but not in the other two groups. In other studies similar results were reported; for example, Schjoedt et al 23 and Saklayen et al 26 showed that spironolactone could decrease GFR, and in a study by van den Meiracker et al, 24 spironolactone caused a transient decrease of GFR. Similarly, Bianchi et al 21 showed that the reduction of GFR due to spironolactone is transient, and after one year of constant use GFR was higher than in the placebo group.…”
Section: Discussionsupporting
confidence: 69%
“…GFR was decreased in the spironolactone group but not in the other two groups. In other studies similar results were reported; for example, Schjoedt et al 23 and Saklayen et al 26 showed that spironolactone could decrease GFR, and in a study by van den Meiracker et al, 24 spironolactone caused a transient decrease of GFR. Similarly, Bianchi et al 21 showed that the reduction of GFR due to spironolactone is transient, and after one year of constant use GFR was higher than in the placebo group.…”
Section: Discussionsupporting
confidence: 69%
“…From a total of 236 potentially eligible studies, 220 were excluded because they were not relevant to the study objectives; were reviews, meeting abstracts, case-only studies (ie, a control group [in which control medication or placebo was added to standard AD/RP/AHT treatment] was not included); or contained no detailed, usable data necessary for the meta-analysis. A total of 16 studies 23,28,34,35,[42][43][44][45][46][47][48][49][50][51][52][53] were included in the present metaanalysis and are described in the table (see also Supplemental Tables 1A-3B in the online version 28,34,43,45,47,49,52,53 ; and hyperkalemia, 12 studies (spironolactone, 319; control, 295). 28,34,35,[43][44][45][46]48,49,50,52,53 Effects of the Addition of Spironolactone on Urinary Protein/Albumin Excretion Compared with controls, the addition of spironolactone to standard AD/RP/AHT treatment significantly reduced end-of-treatment 24-hour urinary albumin/protein excretion (MD = -61.48; 95% CI, -96.74 to -26.23; P = 0.0006) (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…The mineralocorticoid receptor antagonists' spironolactone and eplerenone reduce proteinuria when administered alone with additional antiproteinuric benefits when given with ACEi or ARBs in patients with DMT1 and DMT2. [82][83][84][85][86][87][88][89][90][91][92][93] This additive antiproteinuric benefit is independent of further BP reduction. 86,87,93 The lack of sexual side-effects of eplerenone makes it a good alternative to spironolactone, particularly in men.…”
Section: Blood Pressure Controlmentioning
confidence: 91%